Pengaruh Kualitas Pelayanan dan Peningkatan Pendapatan untuk Membangun Strategi Branding Makanan dalam Membentuk Citra Merek: Studi Kasus Perusahaan Gacoan - Arianto, Ananda Rizki; Melani, Finna Anggun; Yuliani, Tiyas Eka; Qoirunisya, Marshelia Alya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of service quality and revenue increase in building a food branding strategy to form a brand image, with a case study at Gacoan Company. Good service quality and effective revenue increase strategies play an important role in creating customer loyalty and strengthening brand identity in the food industry. The research method used is a quantitative approach with data collection through a survey of Gacoan customers. Data analysis was carried out using statistical methods to see the relationship between service quality variables, revenue increase, and brand image. The results of the study indicate that excellent service quality has a positive impact on customer satisfaction, which ultimately increases loyalty and brand image. In addition, revenue increase strategies such as promotions and menu diversification contribute to strengthening the brand's position in the market. The conclusion of this study is that the combination of quality service and the right marketing strategy plays a significant role in building a strong brand image. Therefore, companies need to continue to improve service standards and develop innovative business strategies to remain competitive in the fast food industry.